Sociology and Literature: Notes on an Ambivalent Affinity - Ivana Spasić (Etnoantropološki Problemi)
The paper begins with Wolf Lepenies’ idea of sociology as a “third culture“, positioned between science and the humanities. Lepenies argues that sociology arose in the 19th century in the context of a bitter rivalry with literature, as both contestants sought to become the principal guide in helping humanity find its way in the new, modern society ushered in by political and industrial revolutions of the late 18th and early 19th centuries. This competition forced sociology to seek legitimacy at the opposite side by borrowing epistemological principles from natural science, which eventually resulted in sociology’s irremediably “middle“ position, which has defined it ever since. The paper focuses on one side of the triangle only, i.e. the relation of sociology to literature, and reviews four possible ways in which the affinity between the two has been construed in sociology’s self-reflection and professional practice. 1) One is based on the recognition of similarities in contents, arguing that both speak of essentially the same subject matter – individuals, families and their destinies within society, conveyed through narrative. Here, the 19th century novel is particularly pertinent, with writers such as Balzac, Zola, and Flaubert leading the way. 2) The second form of affinity points to the similarly privileged social position of both disciplines, and the concomitant responsibility that is ascribed to each in redressing social wrongs and changing the social world for the better. Bourdieu’s conceptualization of the issue is discussed as the most fruitful. 3) Third, the category of “writing“ connects them as two different forms of textual production, with both being subject to comparable requirements of style, genre, and rhetoric. Within contemporary sociology, Jeffrey Alexander’s cultural sociology and social constructionism refracted through sociology’s methodological legacy of qualitative analysis are taken as representative in understanding of sociology as close to literary production. 4) The most abstract conceptualization of similarities locates them at the level of cognitive structures, with both literature and sociology seeking to uncover deeper truths hidden under the screen of self-evident conventions and routines of everyday life. Here, the examples are provided by Lahire’s interpretation of Kafka and Boltanski’s argument about parallels between sociology and detective and spy novels, as well as by more general discussions of literature’s stylistic devices that sometimes give it an advantage in capturing aspects of social reality. In conclusion, it is argued that sociology remains a “third culture“ and that a closer and more open-minded reflection on its affinity with literature could help  revitalize its potentials in the contemporary context.